Natural History of Polycystic Ovary Syndrome and New Advances in the Epidemiology - Piltonen, Terhi T.; Arffman, Riikka K.; Joham, Anju E. (Seminars in Reproductive Medicine, 2021)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women, affecting up to 15% of the female population. The natural history of the syndrome is complex, including both androgen exposure in early life and adiposity-driven dysfunction involving also dysregulated, also involving altered hypothalamus–ovarian crosstalk. The manifestations can arise as early as childhood or puberty onward, suggesting that genetic susceptibility is an important etiological factor. In adulthood, women with PCOS present with reproductive, metabolic, and psychological health issues at a population-based level. Epidemiological studies on large datasets offer an excellent opportunity to evaluate health effects and costs related to the syndrome. Hospital or insurance-based datasets are also available; however, the results are not representative of the female population in the community. More longitudinal studies spanning from early childhood to late adulthood are needed to assess the long-term health impact and early manifestations of PCOS. Moreover, the identification of women with PCOS from large datasets can be expensive. Self-reported symptoms or PCOS diagnosis may offer a feasible approach.
Keywords: PCOS; natural history; epidemiology